2012
DOI: 10.1111/j.1600-0897.2012.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

The Immunohistochemical Analysis of Antigens such as RCAS1 and B7H4 in the Cervical Cancer Nest and within the Fibroblasts and Macrophages Infiltrating the Cancer Microenvironment

Abstract: Introduction The presence of the aggressive phenotype of the tumor seems to be indicated by the local infiltration of cancer cells and by the development of metastases in the lymph nodes. This phenotype is related to the intensity of the suppressive profile of the tumor microenvironment. The aim of our study has been to gather information about the expression of both RCAS1 and B7H4 proteins in the macrophages and fibroblasts present within both the microenvironment of cervical cancer tumors and the cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
3
8
1
Order By: Relevance
“…Similar results were previously reported (20). In addition to tumor cells, tumor-infiltrating macrophages (8,15,21) and the endothelial cells of small blood vessels in the cancer microenvironment were also found to constitutively express B7-H4. B7-H4 was also found to be highly expressed on tumor-associated macrophages in the ascites of ovarian cancer patients and may contribute to tumor progression (15).…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were previously reported (20). In addition to tumor cells, tumor-infiltrating macrophages (8,15,21) and the endothelial cells of small blood vessels in the cancer microenvironment were also found to constitutively express B7-H4. B7-H4 was also found to be highly expressed on tumor-associated macrophages in the ascites of ovarian cancer patients and may contribute to tumor progression (15).…”
Section: Discussionsupporting
confidence: 89%
“…15 In one of our previous studies, we found that RCAS1 immunoreactivity levels on the front of the cervical cancer nest were positively correlated with both the FIGO stage and with the extent of the local spread, thus indicating a more aggressive phenotype. 31 In the present study, we found no differences in the serum sRCAS1 levels between early and advanced stage cervical cancer patients. This finding accords with the original report by Sonoda et al 7 However, in a different study by the Japanese group, the authors reported that not all RCAS1-expressing cells secreted sRCAS1 to the blood stream.…”
Section: Discussioncontrasting
confidence: 59%
“…In a further study by Sonoda et al ., RCAS1 over‐expression in cervical cancer samples was positively correlated with invasion of the lymph‐vascular space, multiple lymph node metastases and tumor volume . In one of our previous studies, we found that RCAS1 immunoreactivity levels on the front of the cervical cancer nest were positively correlated with both the FIGO stage and with the extent of the local spread, thus indicating a more aggressive phenotype . In the present study, we found no differences in the serum sRCAS1 levels between early and advanced stage cervical cancer patients.…”
Section: Discussionsupporting
confidence: 52%
“…Receptor-binding cancer antigen expressed on SiSo cells (RCAS1) was discovered in 1996 by Sonoda et al [8] as a membrane protein present on cervical cancer cells. RCAS1 expression was found on a variety of cells, including T, B, and NK cells, and on macrophages, fibroblasts, and human neoplastic cells [9]. RCAS1 acts through the putative receptor, and its main function is related to the induction of selective immunosuppression.…”
Section: Introductionmentioning
confidence: 99%